Sustainable Soil Improvement: Soft Clay Stabilization Using Rice Husk Hush and Waste Spent Catalyst RCC 15 - Sandy D Sagala; Syahril S; Dian Adiputra Purba; Alexandre Marques (Potensi: Jurnal Sipil Politeknik, 2025)
This study explores the chemical stabilization of soft clay soil to enhance its bearing capacity and improve its performance under structural loads. A fixed proportion of Rice Husk Ash (RHA) at 6% by weight was combined with varying amounts of spent catalyst RCC 15 (5%, 7%, 9%, and 11%) as stabilizing agents. The experimental program included the characterization of soil index properties, followed by engineering tests with emphasis on Unconfined Compressive Strength (UCS), Atterberg limits, compaction characteristics, and California Bearing Ratio (CBR). The Atterberg limit tests indicated a consistent reduction in the plasticity index (PI) with increasing RCC content, reflecting improved soil stability. Compaction results showed an increase in Maximum Dry Density (MDD) and a decrease in Optimum Moisture Content (OMC), with the highest MDD (13.29 kN/m³) and an OMC of 25.67% achieved at 6% RHA and 11% RCC. UCS values increased progressively, reaching a maximum of 1.822 kg/cm² with the same mixture. CBR results further supported these findings, with unsoaked values increasing from 4.75% to 6.60%, and soaked values from 3.30% to 6.20%. The combined use of RHA and RCC 15 significantly improves the geotechnical properties of soft clay, highlighting its potential as a sustainable and effective construction material.